THE EFFECT OF FOREIGN DIRECT INVESTMENT AND FOREIGN PORTFOLIO INVESTMENT ON STOCK MARKET RETURN IN SAARC COUNTRIES - Khan, Mirwais; Rasheed, Shahid; Ullah, Hameed; Ullah, Hayat; Ullah Jan, Kaleem; Alam, Saddam; Qazi, Umer; Mahboobullah (The journal of contemporary issues in business and government, 2022)
The purpose of this study is to examine the influence of foreign direct investment (FDI) and foreign portfolio investment (FPI) on stock market returns (SMR) in SAARC member nations between 2014 and 2019. The World Development Indicators (WDI) and the global economy provided secondary data for this study. Numerous punitive procedures, like the Shapiro-Wilk wtest for determining data normality and the Breusch-pagan test for determining heteroscedasticity, were utilised for robust data analysis. The findings reveal that all FDI and FPI had a low correlation with stock market returns; additionally, the low correlation indicates that the variables included in the current analysis did not exhibit multicollinearity. Diagnostic tests, including the Hausman test, revealed that the author should use the random effect model to analyse the data. The coefficient of FDI was shown to be negatively significant, meaning that increasing FDI reduces stock market returns. Growth in FPI, on the other hand, increased stock market returns. Additionally, the results suggested that the model as a whole is well-fitting.